Polyvinyl acetal resin composition
By controlling the relative amount of residual aldehyde and alkanol in the polyvinyl acetal resin, and adopting a post-treatment process for reduction reaction under high temperature and high pressure conditions, the problem of yellowing of the resin film and the reduction of durability is solved, and the color stability and durability of the resin composition are improved.
Patent Information
- Application Number
- CN202210365165.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-05-08
- Filing Date
- 2018-09-05
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2038-09-05
AI Technical Summary
The existing polyvinyl acetal resins are prone to form side reaction products during the preparation process, resulting in yellowing of the resin film and reduced durability.
By controlling the relative amount of residual aldehyde and alkanol in the polyvinyl acetal resin, the reduction reaction post-treatment process under high temperature and high pressure conditions is adopted to reduce the generation of acidic substances, thereby preparing a resin composition that is not prone to yellowing and has improved durability.
The color stability and durability of the polyvinyl acetal resin film are achieved, which avoids the occurrence of yellowing and improves the overall performance of the resin.
Smart Images

Figure GDF0000035873330000061 
Figure GDF0000035873330000062 
Figure GDF0000035873330000063
Abstract
Description
Technical Field
[0001] The present invention relates to a polyvinyl acetal resin composition, and more particularly to a resin composition for preparing a polyvinyl acetal intermediate film which does not substantially yellow and has improved durability. Background Art
[0002] Generally, laminated glass (tempered glass, safety glass) composed of a pair of glass panels and a synthetic resin film inserted between the panels has excellent safety because glass fragments will not fly even if broken, and is widely used in window glass of road vehicles such as automobiles and window glass of high-rise buildings. Polyvinyl acetal resin with high affinity for inorganic materials is often used in the film suitable for such laminated glass.
[0003] Polyvinyl acetal resin is prepared by a method of acetalization reaction of polyvinyl alcohol and aldehyde. In the commercial process, in order to improve the production efficiency of the polyvinyl acetal resin, there are many cases of adding excess materials compared to the reaction molar amount, and sometimes unexpected side reaction products are formed due to such excessive addition of materials and other reasons. Moreover, these side reaction products affect the color and durability of synthetic resin films. Therefore, it is very important to effectively remove these side reaction products. In response to these problems, Patent Document 1 discloses a process of heat treating a resin slurry, and Patent Document 2 discloses a method of specifying the hydrogen ion concentration of an acid catalyst and performing acetalization reaction under high temperature and high pressure conditions.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Publication No. 5588091, Polyvinyl acetal resin and preparation method thereof
[0007] Patent Document 2: Japanese Patent Gazette No. 5926602, Preparation Method of Polyvinyl Acetal Resin and Polyvinyl Acetal Resin Summary of the invention
[0008] An object of the present invention is to provide a polyvinyl acetal resin composition which does not substantially yellow and has improved durability, and an interlayer film for lamination containing the same.
[0009] The polyvinyl acetal resin composition of one embodiment of the present invention comprises polyvinyl acetal, aldehyde and alkanol, and comprises 50 parts by weight or more of the alkanol based on 100 parts by weight of the aldehyde. The aldehyde may comprise n-butyraldehyde, and the alkanol may comprise 2-ethylhexanol.
[0010] The polyvinyl acetal may be a first polyvinyl acetal having a hydroxyl content of 30 mol % or more and an acetyl content of less than 2 mol %.
[0011] The polyvinyl acetal may be a second polyvinyl acetal having a hydroxyl content of 40 mol % or less and an acetyl content of 8 mol % or more.
[0012] The polyvinyl acetal may be prepared by an acetalization reaction of polyvinyl alcohol and the aldehyde.
[0013] The aldehyde is the residual aldehyde from the acetalization reaction between polyvinyl alcohol and aldehyde.
[0014] The alkanol is derived from the residual aldehyde.
[0015] In the laminated intermediate film prepared using the polyvinyl acetal resin composition, the content of alkanoic acid derived from the reaction product of the residual aldehyde is 2.0%wt% or less, based on the total of the residual aldehyde and the reaction product derived from the residual aldehyde, i.e., the entire reference substance.
[0016] The laminated intermediate film of another embodiment of the present invention includes a first layer, wherein the first layer contains a first polyvinyl acetal, an aldehyde and a plasticizer, and the first layer contains i) the aldehyde and ii) a reaction product derived from the aldehyde, and the content of the alkanoic acid contained in the first layer is less than 2.0wt% based on the sum of the reaction products of i) the aldehyde and ii) the aldehyde, that is, the entire reference substance.
[0017] The aldehyde may comprise n-butyraldehyde and the alkanoic acid may comprise 2-ethylhexanoic acid.
[0018] The reference substance may include i) the n-butyraldehyde, ii) the 2-ethylhexanoic acid, and iii) one selected from the group consisting of 2-ethyl-2-hexenal, 2-ethylhexanal, 2-ethylhexanol, and a combination thereof.
[0019] The first layer may include 58 to 80 parts by weight of the first polyvinyl acetal and 20 to 42 parts by weight of the plasticizer.
[0020] The intermediate film may further include a second layer, wherein the second layer is located on the first layer and includes the second polyvinyl acetal and a plasticizer.
[0021] The second layer may include 58 to 69 parts by weight of the second polyvinyl acetal and 31 to 42 parts by weight of the plasticizer.
[0022] The yellowness index of the first layer may be 3.0 or less.
[0023] The first polyvinyl acetal may be prepared by an acetalization reaction of polyvinyl alcohol and the aldehyde.
[0024] The first layer may comprise an alkanol as the reaction product.
[0025] A laminated glass according to still another embodiment of the present invention includes a laminated body including a first glass located on one surface of the above-mentioned interlayer film for lamination and a second glass located on the other surface of the interlayer film.
[0026] The polyvinyl acetal composition of the present invention and the lamination interlayer film containing the same can provide a composition for preparing a polyvinyl acetal interlayer film which does not substantially yellow and has improved durability. DETAILED DESCRIPTION
[0027] The embodiments of the present invention are described in detail below so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in many different ways and is not limited to the embodiments described here.
[0028] The terms "about", "substantially" and the like used throughout the specification are intended to mean a numerical value or a value close to that numerical value when the inherent preparation and material tolerances are set forth in the referenced meaning, and are used to prevent disclosures that mention exact or absolute numerical values to aid in understanding the present invention from being exploited by unscrupulous infringers.
[0029] Throughout the specification, the term "combination thereof" included in the expression of Markush form refers to a mixture or combination of one or more selected from the group consisting of the constituent elements described in the expression of Markush form, and means that one or more selected from the group consisting of the above constituent elements are included.
[0030] Throughout the specification, the description of "A and / or B" means "A, B, or A and B".
[0031] Throughout the specification, unless otherwise stated, the terms "first", "second" or "A", "B" etc. are used to distinguish the same terms from one another.
[0032] In this specification, "B is located on A" means that B is located on A in a manner abutting against A, or that B is located on A with another layer sandwiched between A and B, and is not limited to the meaning that B is located on A in a manner abutting against the surface of A.
[0033] In the present specification, unless otherwise specified, a singular expression indicates a clearly different meaning according to the context, and a singular expression is interpreted as including the singular or the plural as interpreted according to the context.
[0034] The inventors of the present invention have confirmed in the research of reducing the yellowing phenomenon of polyvinyl acetal film and improving the durability of the film that in the extrusion molding process of polyvinyl acetal film at a relatively high temperature, trace amounts of acidic substances will affect the occurrence of yellowing and the reduction of durability, and have completed the present invention by identifying and reducing these acidic substances. In addition, the inventors of the present invention have confirmed that by controlling the amount of residual alkyl alcohol in the resin during the synthesis process of the polyvinyl acetal resin, the content of acidic substances (alkanoic acid) in the prepared polyvinyl acetal film can be adjusted, and the yellowing degree and durability of the film can be improved, thereby completing the present invention.
[0035] The polyvinyl acetal composition of the present invention comprises polyvinyl acetal, aldehyde and alkanol, and comprises 50 parts by weight or more of the alkanol based on 100 parts by weight of the aldehyde.
[0036] The aldehyde contained in the composition may be a residual aldehyde resulting from an acetalization reaction between polyvinyl alcohol and the aldehyde.
[0037] The alkanol comprises an alkanol derived from the residual aldehyde.
[0038] The aldehyde has a chemical formula of R1CHO, and the R1 may be hydrogen or propyl.
[0039] The alkanol has a chemical formula of R2CH2OH, and the R2 may be a methyl group or an ethylpentyl group.
[0040] The content of the alkanol may be about 50 parts by weight to about 10,000 parts by weight based on about 100 parts by weight of the aldehyde.
[0041] The content of the alkanol may be about 50 parts by weight to about 400 parts by weight based on about 100 parts by weight of the aldehyde.
[0042] The content of the alkanol may be about 70 parts by weight to about 200 parts by weight based on about 100 parts by weight of the aldehyde.
[0043] When a polyvinyl acetal composition containing alkanol in the above-mentioned content range relative to aldehyde is applied to film preparation, the alkanol with a relatively low boiling point can be easily removed during the preparation process of the polyvinyl acetal film at a relatively high temperature, and a polyvinyl acetal film with almost no acidic components or very little acidic components in the film can be prepared.
[0044] The acetate used in the synthesis of the polyvinyl acetal may be selected from the group consisting of n-butanal, isobutyraldehyde, n-valeraldehyde, 2-ethylbutyraldehyde, n-hexanal, and combinations thereof. Specifically, in order to prepare polyvinyl butyraldehyde, n-butyraldehyde may be used as the acetate. In this case, when the polyvinyl acetal resin is used in an interlayer film for glass lamination, there are advantages that the difference in refractive index between the glass to be bonded and the film is small and the bonding strength with the glass is excellent.
[0045] In the commercial process of synthesizing polyvinyl acetal, an excess amount of aldehyde is added compared to the stoichiometric molar number for production efficiency, and the aldehyde remaining after the reaction undergoes aldol condensation, reduction, oxidation and other processes to form aldehyde-derived reaction products, which may be contained in the polyvinyl acetal composition. Moreover, among these reaction products, acidic substances in particular may cause yellowing or reduced durability of the prepared polyvinyl acetal film.
[0046] Although various attempts have been made to control the absolute amount of the acidic substance contained in the polyvinyl acetal composition by washing or the like, problems such as yellowing of the produced film and reduction in durability have occurred.
[0047] In this regard, in the present invention, by controlling the relative amounts of the components contained in the polyvinyl acetal composition, even if there is an excess of residual aldehyde such as butyraldehyde in the synthesized polyvinyl acetal resin, the color and durability of the polyvinyl acetal film will not be deteriorated.
[0048] That is, in the present invention, in the process of preparing polyvinyl acetal, a post-treatment step of inducing a reduction reaction of residual aldehyde and its reaction product using a catalyst, a reducing atmosphere, etc. is performed to prepare a polyvinyl acetal composition having a relatively large alkanol content compared to the aldehyde content.
[0049] The reduction reaction in the post-treatment step may be performed in the presence of a catalyst. Specifically, a copper chromite catalyst, a nickel catalyst, a rhodium catalyst, etc. may be used as the catalyst, but the present invention is not limited thereto.
[0050] The reduction reaction in the post-treatment process can be carried out in a reducing atmosphere, for example, the reaction can be carried out in a hydrogen-nitrogen atmosphere at high temperature and high pressure. Specifically, the reaction can be carried out at a reaction temperature of 140 to 200° C. and a reaction pressure of 5 to 30 bara.
[0051] When these catalyst conditions and high temperature and high pressure conditions are applied to the post-treatment process, the efficiency of the process can be further improved.
[0052] In particular, when n-butylaldehyde (the following Chemical Formula 1) is used as the aldehyde, the reaction products of the aldehyde remaining after the resin synthesis are shown in the following Chemical Formulas 2 to 5.
[0053] [Chemical formula 1]
[0054]
[0055] [Chemical formula 2]
[0056]
[0057] [Chemical formula 3]
[0058]
[0059] [Chemical formula 4]
[0060]
[0061] [Chemical formula 5]
[0062]
[0063] Among the reaction products, 2-ethylhexanoic acid (Chemical Formula 5) as an alkanoic acid is an acidic substance generated by oxidation of 2-ethylhexanal (Chemical Formula 3) as one of the reaction products derived from the aldehyde of Chemical Formula 1. In contrast, 2-ethylhexanol (Chemical Formula 4) as an alkanol is formed by reduction of the 2-ethylhexanal (Chemical Formula 3).
[0064] The polyvinyl acetal composition of the present invention may contain n-butyraldehyde as the aldehyde, and may contain 2-ethylhexanol as the alkanol.
[0065] In the polyvinyl acetal composition, based on 1 part by weight of the 2-ethylhexanol content, the n-butyraldehyde content may be 0.5 parts by weight, may include 0.5 to 4 parts by weight, may include 0.6 to 3 parts by weight, or may include 0.7 to 2 parts by weight.
[0066] In the case of the polyvinyl acetal composition having such characteristics, the reaction product of the residual aldehyde is finally formed in a reduced form rather than an oxidized form, so the generation of acidic components is very small, and the reduced form reaction product having a lower boiling point is easily removed into the air during the film preparation process performed at a high temperature, so that a polyvinyl acetal film having a small acidic component content in the prepared polyvinyl acetal composition and improved durability can be prepared.
[0067] The polyvinyl acetal may be a polyvinyl acetal obtained by acetalizing polyvinyl alcohol having a degree of polymerization of 1,600 to 3,000 with an aldehyde.
[0068] The polyvinyl acetal may be a first polyvinyl acetal having a hydroxyl content of 30 mol% or more and an acetyl content of less than 2 mol%, and a hydroxyl content of 30 to 50 mol%. The polyvinyl acetal having such characteristics can prepare a polyvinyl acetal film having excellent bonding strength with glass and excellent mechanical strength.
[0069] The polyvinyl acetal may be a second polyvinyl acetal having a hydroxyl content of 40 mol% or less and an acetyl content of 8 mol% or more, and a hydroxyl content of 1 to 10 mol%. The polyvinyl acetal having such characteristics can prepare a polyvinyl acetal film having sound insulation characteristics.
[0070] The polyvinyl acetal is prepared by an acetalization reaction of polyvinyl alcohol and the aldehyde.
[0071] Another embodiment of the laminated intermediate film of the present invention includes a first layer, which includes a first polyvinyl acetal, an aldehyde and a plasticizer, wherein the first layer includes i) the aldehyde and ii) a reaction product derived from the aldehyde, and the content of the alkanoic acid contained in the first layer is less than 2.0wt% based on the sum of the reaction products of i) the aldehyde and ii) the aldehyde, i.e., the entire reference substance.
[0072] Based on the sum of i) the aldehyde and ii) the reaction product of the aldehyde, that is, the entire reference substance, the content of the alkanoic acid contained in the first layer may be 1.0 wt % or less, may be 0.5 wt % or less, and may be 0.00001 to 1.0 wt %.
[0073] When the alkanoic acid is contained within such a content range, even if residual aldehyde is present, the interlayer film has low yellowness and excellent durability, and thus can be provided as a lamination interlayer film with excellent characteristics.
[0074] The aldehyde as the reaction residue of the acetalization reaction may form various reaction products as described above. The reaction product of the aldehyde may contain a carbonyl group or a hydroxyl group in the molecule and may include an aldol condensation reaction product.
[0075] The alkanoic acid is one of these reaction products, is an acidic substance, and may have the chemical formula of R3COOH (wherein R3 is methyl or ethylpentyl).
[0076] The aldehyde may comprise n-butyraldehyde and the alkanoic acid may comprise 2-ethylhexanoic acid.
[0077] At this time, the substance (reference substance) serving as the reference for the alkanoic acid content is the residual aldehyde and its reaction product, specifically, i) the n-butyraldehyde, ii) the 2-ethylhexanoic acid and iii) one selected from the group consisting of 2-ethyl-2-hexenal, 2-ethylhexyl aldehyde, 2-ethylhexanol and a combination thereof.
[0078] The 2-ethylhexanoic acid, 2-ethyl-2-hexenal, 2-ethylhexyl aldehyde or 2-ethylhexanol may be derived from the residual n-butyraldehyde, and part of the material is substantially not detected due to being removed during the above-mentioned post-treatment steps and film preparation process.
[0079] The first layer may include 58 to 80 parts by weight of the first polyvinyl acetal and 20 to 42 parts by weight of the plasticizer.
[0080] The first layer may contain 60 to 75 parts by weight of the first polyvinyl acetal and 25 to 40 parts by weight of the plasticizer. In this case, the first layer can be used as a surface layer, which not only has excellent bonding strength with a transparent laminate such as glass, but also can impart excellent mechanical strength to laminated glass and the like.
[0081] The intermediate film may further include a second layer, wherein the second layer is located on the first layer and includes the second polyvinyl acetal and a plasticizer.
[0082] The second layer may include 58 to 69 parts by weight of the second polyvinyl acetal and 31 to 42 parts by weight of the plasticizer.
[0083] When the intermediate film includes the second layer, the second layer can function as a sound insulation layer, and the intermediate film including the second layer can have excellent mechanical strength and excellent sound insulation performance.
[0084] The weight average molecular weight of the second polyvinyl acetal may be 400,000 or more, 490,000 to 850,000, 610,000 to 820,000, or 690,000 to 790,000.
[0085] When the weight average molecular weight of the second polyvinyl acetal is 490,000 or more, the machine performance of the intermediate film can be improved, and the co-extrusion workability and the compatibility of the composition can be further improved.
[0086] The lamination intermediate film may have a three-layer structure of a first layer-a second layer-a first layer.
[0087] The intermediate film may further include a third layer, wherein the third layer is located between the first layer and the second layer and includes a third polyvinyl acetal and a plasticizer.
[0088] The third layer may include 58 to 80 parts by weight of the first polyvinyl acetal and 20 to 42 parts by weight of the plasticizer.
[0089] The hydroxyl amount of the third polyvinyl acetal may have a value between the hydroxyl amount of the first polyvinyl acetal and the hydroxyl amount of the second polyvinyl acetal.
[0090] The laminating intermediate film may have a five-layer structure of first layer-third layer-second layer-third layer-first layer.
[0091] When a five-layered interlayer film is prepared as described above, it is possible to provide an interlayer film for lamination that has excellent sound insulation properties in a wider temperature range, has reduced interlayer heterogeneity, and significantly reduces interlayer delamination.
[0092] The yellowness index of the interlayer film for lamination may be 3.0 or less, or 2.5 or less, and may be 0.1 to 2.5, or 0.1 to 1.5.
[0093] These yellowness indices are based on measurements made in accordance with ASTM E313. An interlayer film having the above yellowness indices has a relatively low yellowness index, is excellent in transparency and color properties, and can have excellent durability.
[0094] The difference in yellowness of the laminated interlayer before and after the accelerated aging test (744 hours basis) of d-YI evaluation may be less than 3.
[0095] Specifically, the yellowness index of the first layer may be 3.0 or less, or 2.5 or less, or the yellowness index may be 0.1 to 2.5, or 0.1 to 1.5.
[0096] Specifically, the yellowness index of the second layer may be 3.0 or less, or 2.5 or less, or the yellowness index may be 0.1 to 2.5, or 0.1 to 1.5.
[0097] Specifically, the yellowness index of the third layer may be 3.0 or less, or 2.5 or less, or the yellowness index may be 0.1 to 2.5, or 0.1 to 1.5.
[0098] The first to third layers can be prepared by using a polyvinyl alcohol resin having the above alkanol content characteristics to form each layer having the above characteristics.
[0099] Specifically, the plasticizer can be selected from the group consisting of triethylene glycol bis-2-ethylene hexanoate (3G8), tetraethylene glycol diheptanoate (4G7), triethylene glycol bis-2-ethyl butyrate (3GH), triethylene glycol bis-2-heptanoate (3G7), dibutoxyethoxyethyl adipate (DBEA), butyl carbitol adipate (DBEEA), dibutyl sebacate (DBS), di-2-hexyl adipate (DHA) and mixtures thereof, and more specifically, triethylene glycol bis-2-ethylene hexanoate (3G8) can be used as the plasticizer. The plasticizers used for each layer can be the same, or different plasticizers can be used for each layer.
[0100] The lamination interlayer film may further contain an additive selected from the group consisting of an antioxidant, a heat stabilizer, an ultraviolet (UV) absorber, an ultraviolet stabilizer, an infrared (IR) absorber, a glass bonding strength regulator, and a combination thereof, as necessary.
[0101] The additive may be included in at least one of the first to third layers. By including the additive, the long-term durability of the film such as thermal stability and light stability and the anti-scattering performance can be improved.
[0102] The antioxidant may be a hindered amine or a hindered phenol. Specifically, in the preparation process of polyvinyl butyral (PVB) which requires a process temperature of 150° C. or higher, a hindered phenol antioxidant is more preferred. Hindered phenol antioxidants may include, for example, IRGANOX 1076 and 1010 of BASF, Germany.
[0103] When considering compatibility with an antioxidant, the heat stabilizer may be a phosphite heat stabilizer, for example, IRGAFOS168 produced by BASF of Germany.
[0104] The ultraviolet absorber may include Chemisorb 12, Chemisorb 79, Chemisorb 74, Chemisorb 102 from Chemipro KASEI, and Tinuvin 328, Tinuvin 329, Tinuvin 326 from BASF, Germany. The UV stabilizer may include Tinnafin from BASF, Germany. As the infrared absorber, indium tin oxide (ITO), antimony tin oxide (ATO), aluminum-doped zinc oxide (AZO), etc. may be used, and as the glass bonding strength regulator, metal salts of Mg, K, Na, etc., epoxy-modified silicone oil, or a mixture thereof may be used, but the present invention is not limited thereto.
[0105] The total thickness of the intermediate film may be greater than 0.4 mm, specifically, 0.4 to 1.6 mm, 0.5 to 1.2 mm, or 0.6 to 0.9 mm. In view of the minimum regulatory performance and cost, the above thickness range is suitable.
[0106] The intermediate film may be composed of the first layer, or may include the first layer.
[0107] The thickness of the second layer in the intermediate film may be 0.04 to 0.20 mm, 0.07 to 0.18 mm, or 0.09 to 0.15 mm.
[0108] The thickness of the third layer in the intermediate film may be 0.1 mm or less, or 0.09 mm or less, or 0.001 to 0.1 mm, or 0.001 to 0.08 mm, or 0.001 to 0.3 mm.
[0109] The intermediate film may have a loss coefficient of 0.35 or more, the loss coefficient being measured at a temperature of 20° C. and a frequency of 2,000 to 4,000 Hz based on a total thickness of 800 μm of the intermediate film including the second layer.
[0110] A laminated glass according to still another embodiment of the present invention includes a laminate including a first glass located on one surface of the above-mentioned laminating interlayer film and a second glass located on the other surface of the laminating interlayer film.
[0111] The first glass and the second glass are transparent plate-shaped glasses, and materials such as light-transmitting plastics may be used to replace part or all of the first glass and the second glass.
[0112] The laminated glass can be used for automobile glass, interior materials or exterior materials of buildings, etc., and has low yellowness and excellent durability.
[0113] In the following experimental description, when the unit is unclear about % and it is unclear whether the % is wt% or mol%, the unit refers to wt%.
[0114] 1) Synthesis of polyvinyl acetal
[0115] (Synthesis of Resin 1)
[0116] 30 g of polyvinyl alcohol (PVA) having a degree of polymerization of 1700 and a degree of saponification of 99% was added to 570 g of distilled water at 90° C. to prepare a 5.00 wt % polyvinyl alcohol aqueous solution, and the aqueous solution was added to the reactor. After the reactor temperature was lowered to 17° C., 38.57 g of hydrochloric acid having a purity of 37 mol % was added as a catalyst, and while the reactor temperature was maintained at 50 to 55° C., 29.7 g of n-butyraldehyde was added in small portions, and polyvinyl alcohol synthesis was performed for 3 hours.
[0117] After the polyvinyl alcohol synthesis reaction was fully carried out, the temperature of the reactor was lowered to 20° C., and sodium hydroxide (NaOH) was added in small portions until the pH was 10 and neutralized for 1 hour to obtain a polyvinyl butyral (PVB) resin of a solid state resin 1.
[0118] The polyvinyl butyral resin of the resin 1 was washed with distilled water. Specifically, the amount of distilled water was set to 10 times that of the polyvinyl butyral resin, and the washing was repeated 5 times with water. Then, the resin 1 was dried with hot air to remove moisture, thereby obtaining a powdered resin 1.
[0119] (Synthesis of Resin 2)
[0120] The resin prepared as described above (synthesis of resin 1) was treated in a high-temperature and high-pressure container at 170°C and 6 bara in a reducing atmosphere of H2 / N2 for 5 hours, and then subjected to steps such as water washing to synthesize resin 2.
[0121] (Synthesis of Resin 3)
[0122] Resin 1 prepared as described above (Synthesis of Resin 1) was treated in a high-temperature and high-pressure container at 170°C and 6 bara in a reducing atmosphere of H2 / N2 for 10 hours, and then subjected to steps such as water washing to synthesize Resin 3.
[0123] 2) Hexanol content relative to butyraldehyde content in the resin
[0124] The content of n-butyraldehyde and the relative amount of 2-ethyl-hexanol in the sample were confirmed using Thermal Desorption-Gas Chromatograph / Mass Spectrometer (TD-GC / MS).
[0125] Specifically, about 0.04 g of a resin powder sample was taken and passed through the first heating desorption section and the second heating desorption section in a TD (JAI's JTD-505Ⅲ). The following conditions were applied: temperature was 150°C (PAT) and -40°C (cold trap), PAT heating time was 15 minutes, SAT desorption time was 3 minutes, and the split ratio was 1 / 50.
[0126] The samples passed through the TD were separated and detected by GC-MS. Specifically, Agilent Technologies 7890B (GC) and 5977A (MS) using HP5MS columns (0.25 mm × 30 m × 0.25 μm) were used for the experiment, and the following conditions were applied: oven: 40°C (hold for 5 minutes) -10°C / min -280°C (hold for 5 minutes) -10°C / min -300°C (hold for 9 minutes).
[0127] As a result of the detection, the target substance was detected between 2 minutes and 15 minutes. Specifically, after confirming n-butyraldehyde (RT2.58), 2-ethyl-hexanal (RT10.87), 2-ethyl-2-hexenal (RT11.88), 2-ethyl-hexanol (RT12.49), and 2-ethylhexanoic acid (RT14.14), peak integration was performed, and the content of 2-ethylhexanol relative to n-butyraldehyde was quantified in ppm, and then the ratio was confirmed (see Table 1 below).
[0128] 3) Preparation of polyvinyl acetal film
[0129] A composition containing 0.1wt% IRGANOX 1010 and 0.1wt% IRGAFOS168 as antioxidants, 0.03wt% (30ppm) magnesium acetate and 0.03wt% (30ppm) potassium acetate as bonding strength regulators, 0.3wt% tinuvin P as a UV blocker, 27.5wt% triethylene glycol bis-2-ethylenehexanoate (3G8) as a plasticizer and a residual amount of 100wt% of the total of resins 1 to 3 which are polyvinyl alcohol acetal resins is added, and the sheets 1 to 3 of a single-layer intermediate film with a thickness of 760μm are obtained by extrusion molding at 200°C using a biaxial stretching machine and casting using a T-die.
[0130] 4) Hexanol content relative to butyraldehyde content of the sheet
[0131] The analysis was performed in the same manner as in the above-mentioned 3) detection of the content of the resin, but unlike the case of the resin, in the sheet, about 0.5 g of the sample was applied to the analysis.
[0132] The results were analyzed in the same manner as in the above 3), and after peak integration was performed, the content ratio of 2-ethylhexanoic acid was confirmed (see Table 1 below).
[0133] 5) Quantitative analysis of 2-ethylhexanoic acid in sheets
[0134] The butyraldehyde-derived reaction byproducts in the bonding film were analyzed using TD-GC / MS. 0.5 g of the films prepared in the examples and comparative examples were taken out respectively and passed through the first heating desorption section and the second heating desorption section in the TD (JAI's JTD-505Ⅲ). The following conditions were applied: temperature was 150°C (PAT) and -40°C (cold trap), PAT heating time was 15 minutes, and SAT desorption time was 3 minutes. The split ratio was 1 / 50.
[0135] The samples passed through TD were separated and detected by GC-MS. Specifically, Agilent Technologies 7890B (GC) and 5977A (MS) using HP5MS columns (0.25 mm × 30 m × 0.25 μm) were used for the experiment, and the following conditions were applied: oven: 40°C (held for 5 minutes) -10°C / min -280°C (held for 5 minutes) -10°C / min -300°C (held for 9 minutes).
[0136] The target substance 2-ethylhexanoic acid (RT14.14) was quantitatively analyzed using an FID detector. First, for quantitative analysis, a standard sample of 2-ethylhexanol was dissolved in three concentrations of 439 ppm, 1131 ppm, and 2695 ppm, and a calibration curve was obtained with the y-axis as the input amount and the x-axis as the peak area, and used as a reference substance.
[0137] Using the calibration curve of 2-ethylhexanol as a reference, relative quantification of n-butyraldehyde (RT2.58) and its reaction products, 2-ethylhexanal (RT10.87), 2-ethyl-2-hexenal (RT11.88), and 2-ethylhexanoic acid (RT14.14), was performed. The results of calculation using the respectively calculated values are shown in Table 1 below.
[0138] 6) Color evaluation of sheets (YI, yellowness index)
[0139] The yellowness index (YI) of the polyvinyl acetal film (sheets 1 to 3) was measured according to ASTM E313. Specifically, a laminate of a laminate structure of a release film-sheet-release film (PET coated with silicone) was bonded in a laminator at 150°C for 15 minutes by heating and pressing to prepare a test piece, and after removing the release film from the test piece, it was measured under the condition of 400 to 800 nm using a measuring instrument of HunterLab, and the results are shown in Table 1 below.
[0140] 7) Durability evaluation of sheets
[0141] (d-YI evaluation method)
[0142] According to KS M ISO 4892-3:2002, an accelerated aging test of the laminated glass was conducted, and the durability was evaluated based on d-YI (yellowing index difference).
[0143] A laminated body was prepared by laminating a 70 mm × 150 mm glass with a thickness of 2.1 mm and the above sheets 1 to 3 as an intermediate film in a glass-intermediate film-glass laminate structure, and pre-bonding and main bonding were performed. The initial value of the yellowness index (YI) at the center of the bonded test piece was measured using a measuring instrument from HunterLab according to ASTM E313. initial After the initial value is determined, the test piece is placed in a QUV device and subjected to a 744-hour accelerated aging test. After the experiment, the final value of the yellowness index (YI final ), and the yellowing degree difference is calculated by the following formula.
[0144] d-YI=YI final -YI initial
[0145] If the obtained value d-YI was 3 or more, it was evaluated as "unacceptable", and if d-YI was less than 3, it was evaluated as "acceptable". The results are shown in Table 1 below.
[0146] 8) Evaluation of the penetration resistance and impact resistance of the sheet
[0147] (Penetration resistance evaluation)
[0148] Evaluate the penetration resistance of laminated glass based on KS L 2007.
[0149] A 300mm×300mm glass with a thickness of 2.1mm and the above-mentioned sheets 1 to 3 as an intermediate film were prepared into a glass-intermediate film-glass laminated structure, pre-joined by vacuum, degassed and edge sealed. After that, the main joining was performed at 150°C for 2 hours using an autoclave to prepare the test piece. Then, a 2.26kg steel ball was dropped on the test piece, and the height (MBH) at which the test piece was penetrated was measured. At this time, if it was penetrated at a height of less than 4m, it was marked as "unqualified", and if it was penetrated at a height of more than 4m, it was marked as "qualified".
[0150] (Impact resistance evaluation)
[0151] According to KS L 2007:2008, the presence or absence of cracks in the laminated glass is evaluated during the impact resistance evaluation.
[0152] In the same manner as the above-mentioned penetration resistance evaluation, a process of preparing and bonding 2.1 mm thick glass and the intermediate films of sheets 1 to 3 into a laminated structure of glass-intermediate film-glass was performed.
[0153] The low-temperature evaluation is carried out as follows: a 227g steel ball is stored at -20°C for 4 hours and then dropped from a height of 9m. If the test piece is broken by the impact and the amount of glass scattered or the amount of glass dropped from the sheet is more than 15g, it is marked as "unqualified". If the test piece is not broken by the impact or the amount of glass scattered and the amount of glass dropped from the sheet is less than 15g, it is marked as "qualified".
[0154] The room temperature evaluation is carried out as follows: a 227 g steel ball is stored at 40°C for 4 hours and then dropped from a height of 10 m. If the test piece is broken by the impact and the amount of glass scattered or the amount of glass dropped from the sheet is more than 15 g, it is marked as "unqualified". If the test piece is not broken by the impact or the amount of glass scattered and the amount of glass dropped from the sheet is less than 15 g, it is marked as "qualified".
[0155] [Table 1]
[0156]
[0157] *Butyraldehyde and its reaction products refer to the butyraldehyde remaining after the preparation of the resin and substances derived therefrom, specifically, butyraldehyde (RT2.58), 2-ethyl-hexanal (RT10.87), 2-ethyl-2-hexenal (RT11.88), 2-ethyl-hexanol (RT12.49) and 2-ethylhexanoic acid (RT14.14).
[0158] Referring to the results in Table 1 above, the content of 2-ethylhexanol relative to n-butyraldehyde in resin 1 is relatively small, and it is estimated that it is polyvinyl butyral with a relatively high content of n-butyraldehyde. In contrast, the ratio of the content (weight parts) of 2-ethylhexanol relative to n-butyraldehyde in resins 2 and 3 is 100:50 or more, and it is estimated that it is polyvinyl butyral with a relatively low content of n-butyraldehyde.
[0159] As described above, n-butyraldehyde is modified during the reaction to generate 2-ethylhexanal as a byproduct, and 2-ethylhexanol is generated through a reduction process of the 2-ethylhexanal, or 2-ethylhexanoic acid is generated through an oxidation process.
[0160] A relatively large amount of 2-ethylhexanoic acid contained in the sheet 1 prepared using the resin 1 is considered to be a substance having high acidity and harmful to the environment, and therefore is considered to affect the yellowness, durability, and the like of the sheet.
[0161] In the case of Sheet 2 and Sheet 3 prepared using Resin 2 and Resin 3, respectively, a relatively small amount of 2-ethylhexanoic acid is contained because a considerable amount of n-butyraldehyde contained in Resin 1 is reduced to 2-ethylhexanol through the reduction process applied to Resin 1 and removed to the air during the sheet preparation process, thereby significantly reducing the content of 2-ethylhexanoic acid in the entire prepared sheet.
[0162] The preferred embodiments of the present invention are described in detail above, but it should be understood that the scope of protection claimed by the present invention is not limited to the above embodiments, but various modifications and improvements made by ordinary technicians in the technical field of the present invention using the basic concepts of the present invention defined in the scope of protection claimed below also fall within the scope of protection claimed by the present invention.
Claims
1. A polyvinyl acetal resin composition, characterized in that Contains polyvinyl acetal, aldehyde and alkanol, The aldehyde is the residual aldehyde from the acetalization reaction of polyvinyl alcohol and aldehyde. Based on 100 parts by weight of the aldehyde, the alkane alcohol contains 50 parts by weight or more. The aldehyde comprises n-butyraldehyde, the alkanol comprises 2-ethylhexanol, In the laminated intermediate film prepared using the polyvinyl acetal resin composition, the content of alkanoic acid derived from the reaction product of the residual aldehyde is 2.0%wt% or less, based on the total of the residual aldehyde and the reaction product derived from the residual aldehyde, i.e., the entire reference substance.
2. The polyvinyl acetal resin composition according to claim 1, characterized in that The polyvinyl acetal is prepared by an acetalization reaction of polyvinyl alcohol and the aldehyde.
3. The polyvinyl acetal resin composition according to claim 1, characterized in that The polyvinyl acetal is a first polyvinyl acetal, wherein the hydroxyl content of the first polyvinyl acetal is greater than 30 mol % and the acetyl content is less than 2 mol %.
4. The polyvinyl acetal resin composition according to claim 1, characterized in that The polyvinyl acetal is a second polyvinyl acetal, and the second polyvinyl acetal has a hydroxyl content of 40 mol % or less and an acetyl content of 8 mol % or more.
5. The polyvinyl acetal resin composition according to claim 1, characterized in that The alkanol is derived from the residual aldehyde.
Citation Information
Patent Citations
Liquid crystal display panel
JP1980088091A
Hydraulic circuit of cylinder
JP1984026602A
Process of purification of polyvinyl acetals
US2859207A